Nickel-based catalytic material as well as preparation method and application thereof
The preparation of nickel-based catalytic materials through seawater corrosion technology has solved the problem of complex catalyst preparation and low selectivity in biomass electrocatalytic oxidation technology, and achieved efficient biomass oxidation conversion and cost reduction.
Patent Information
- Application Number
- CN202411423070.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-02-25
AI Technical Summary
Biomass electrocatalytic oxidation technology faces problems such as complex catalyst preparation process, reliance on precious metals for molecular oxygen activation, and low reaction selectivity and yield.
Nickel-based catalytic materials are prepared by seawater corrosion technology. By adding transition metal salts to seawater and oscillation, oxygen and carbon dioxide in the air participate in the reaction, forming a layered bimetallic alkaline carbonate catalyst to improve catalytic activity and stability.
The specific surface area and number of active sites of the catalytic material are improved, the adsorption capacity and reactivity of the reaction substrate are enhanced, the production cost is reduced, and the efficient conversion of biomass oxidation is achieved.
Smart Images

Figure CN119506950A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomass catalysis, and in particular to a nickel-based catalytic material and a preparation method and application thereof. Background Art
[0002] With the rapid development of society, the consumption of fossil resources and environmental pollution have become increasingly prominent. Replacing high-carbon resources with low-carbon resources and replacing non-renewable resources with renewable resources have become the main ideas for reducing carbon emissions. Biomass is a carrier that has both resource and energy characteristics. Through efficient conversion, biomass can derive a series of high-value chemicals that replace fossil products. For example, 2,5-furandicarboxylic acid (FDCA), as an important bio-based platform compound, is widely used in medicine, fragrances, metal coordination chemistry, etc.; and FDCA has a conjugated carbon ring and diacid structure similar to petroleum-based terephthalic acid (TPA), which can replace TPA for the synthesis of bio-based polyethylene furandicarboxylate (PEF) with better thermal stability and gas barrier properties. It is expected to replace petroleum-based polyethylene terephthalate (PET) materials, reduce environmental pollution and generate huge economic benefits. Another example is 2,5-tetrahydrofurandicarboxylic acid (THFDCA), which is widely used in today's society. It is mainly used in the synthesis of high-performance polymers, providing excellent mechanical properties and flexibility, and replacing petroleum-based products. It not only supports sustainable development and reduces carbon footprint, but also serves as an important raw material for exploring new materials and synthesis methods. At the same time, bio-based materials are biodegradable, providing alternatives for environmentally friendly applications and promoting the transformation of society to sustainable production and consumption methods.
[0003] In recent years, research on biomass electrocatalytic oxidation has made significant progress. Researchers have developed a variety of catalyst systems, including precious metals, transition metals, and non-metallic catalysts. However, biomass electrocatalytic oxidation technology still faces many challenges, such as the complex catalyst preparation process, which makes it difficult to apply it on a large scale; the activation of molecular oxygen usually relies on highly active precious metal catalysis; by-products are easily produced during the reaction, and the selectivity is not strong. Summary of the invention
[0004] In view of the deficiencies of the prior art, the purpose of the present invention is to develop a new biomass electrocatalytic material to improve reaction selectivity and yield and reduce production costs.
[0005] In order to solve the above technical problems, the first aspect of the present invention provides a method for preparing a nickel-based catalytic material, comprising the following steps:
[0006] The nickel foam was ultrasonically cleaned with hydrochloric acid, ethanol and deionized water, and dried for later use;
[0007] The pretreated nickel foam is placed in seawater containing a single transition metal salt and oscillated in a constant temperature oscillator;
[0008] After shaking, the material is taken out from the seawater and rinsed to obtain a nickel-based catalytic material.
[0009] The present invention uses foamed nickel as a base material, adopts seawater corrosion technology to corrode metal nickel into nickel ions, and simultaneously adds other transition metals, and uses oscillation to dissolve oxygen and carbon dioxide in the air in seawater to participate in the reaction, forming hydroxide ions and carbonate ions, which are combined with metal ions, and layered bimetallic basic carbonates are uniformly grown on the surface of the base to provide active sites, so that the nickel-based catalytic material has high catalytic activity and stability.
[0010] Furthermore, the concentration of the transition metal salt in the seawater is 0.5-50 mM. The introduction of the transition metal component improves the adsorption capacity of the catalytic material for the reaction substrate, greatly enhancing the reaction activity of the catalytic material.
[0011] Furthermore, the transition metal salt is selected from one of cobalt chloride, manganese chloride, ferric chloride, molybdenum chloride, chromium chloride and copper chloride.
[0012] Furthermore, the oscillation frequency of the constant temperature oscillator is 100-200 rpm.
[0013] Furthermore, the oscillation time in the constant temperature oscillator is 0.5 to 16 hours.
[0014] Furthermore, the temperature of the constant temperature oscillator is 20-25°C.
[0015] The catalyst on the substrate surface is generated during the oscillation process. The oscillation time, frequency, and temperature will affect the catalyst structure and phase. Therefore, it is necessary to control the oscillation conditions to ensure the generation of bimetallic basic carbonates.
[0016] The second aspect of the present invention provides a nickel-based catalytic material, which is prepared by the above-mentioned preparation method, and the nickel-based catalytic material includes a foamed nickel substrate and a bimetallic basic carbonate catalyst supported on the surface of the foamed nickel substrate. The basic carbonate catalyst and the foamed nickel substrate form a semiconductor-metal heterojunction, which effectively improves the electron transfer path, promotes electron transfer, and improves catalytic activity.
[0017] Furthermore, the bimetallic basic carbonate catalyst has a flower-like nanosheet array structure or a needle-like structure, which enables the catalyst to have a very high specific surface area, increases the number of active sites, enhances adsorption performance, and thus improves catalytic activity.
[0018] The third aspect of the present invention provides an application, using the above nickel-based catalytic material for electrocatalytic oxidation of biomass, wherein the biomass is selected from one of 5-hydroxymethylfurfural, 2,5-furan dimethanol, and 2,5-tetrahydrofuran dimethanol.
[0019] Furthermore, the reaction system of the electrocatalytic oxidation is a three-electrode system, the working electrode is the nickel-based catalytic material, the counter electrode is a platinum electrode or a carbon material electrode, the reference electrode is selected from one of a Hg / HgO reference electrode, a saturated calomel electrode, and an Ag / AgCl reference electrode, the electrolyte is an alkaline solution, the concentration of the biomass is 5 to 100 mM, and the reaction potential is 1.2 to 1.6 V vs. RHE.
[0020] The nickel-based catalytic material of the present invention exhibits excellent activity for biomass oxidation and has good structural stability, and the structure will not be destroyed after the biomass cyclic electrolysis.
[0021] In summary, compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) The present invention prepares the catalytic material through seawater corrosion technology, which can not only increase the specific surface area of the catalytic material and expose more active sites, but also improve the structural stability of the catalytic material.
[0023] (2) The present invention adds transition metal components to seawater, thereby improving the adsorption capacity of the catalytic material for the reaction substrate, and the deposited transition elements have multiple valence states, which can significantly increase the proton affinity and enhance the reaction activity.
[0024] (3) The present invention introduces oxygen and carbon dioxide from the air into the reaction system by oscillation, uniformly grows layered bimetallic basic carbonates on the surface of the substrate, effectively regulates the d-band center position of the catalyst, makes biomass more easily adsorbed on the surface of the catalytic material, improves the electron transmission path, and exhibits excellent activity for biomass oxidation.
[0025] (4) The present invention is simple to operate, highly repeatable, and can obtain highly active catalytic materials without using precious metals. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 1 is a SEM image of different catalytic materials in Example 1 of the present invention.
[0027] Figure 2 These are the HRTEM and SAED images of the nickel-based catalytic material Co-sw / NF in Example 1 of the present invention.
[0028] Figure 3 It is the TG curve diagram and FTIR curve diagram of the nickel-based catalytic material Co-sw / NF in Example 1 of the present invention.
[0029] Figure 4 1 is a current density diagram and an LSV curve diagram of different catalytic materials in Example 1 of the present invention.
[0030] Figure 5It is a current density diagram and LSV curve diagram of the nickel-based catalytic material prepared with different transition metal salt concentrations in Example 2 of the present invention.
[0031] Figure 6 It is a current density diagram and LSV curve diagram of the nickel-based catalytic material prepared at different corrosion times in Example 3 of the present invention.
[0032] Figure 7 3 is the LSV curve diagram of the nickel-based catalytic materials Co-sw / NF and Mn-sw / NF at different HMF concentrations in Example 4 of the present invention.
[0033] Figure 8 This is a graph showing the product analysis results of the nickel-based catalytic material Co-sw / NF at different electrolysis potentials in Example 5 of the present invention.
[0034] Fig. 9 This is a diagram of the catalytic process of the nickel-based catalytic material Co-sw / NF at different electrolysis potentials in Example 5 of the present invention.
[0035] Fig.10 This is a diagram of the catalytic process of the nickel-based catalytic material Mn-sw / NF in Example 6 of the present invention.
[0036] Fig.11 This is a graph showing the product analysis results of cyclic electrolysis of HMF under constant potential using the nickel-based catalytic material Co-sw / NF in Example 7 of the present invention.
[0037] Fig.12 This is a curve diagram of the potential change of the nickel-based catalytic material Co-sw / NF under constant current density in Example 8 of the present invention.
[0038] Fig.13 This is a diagram of the catalytic process of electro-oxidation of BHMF by the nickel-based catalytic material Co-sw / NF in Example 9 of the present invention.
[0039] Fig.14 This is a diagram of the catalytic process of electro-oxidation of THFDM by the nickel-based catalytic material Co-sw / NF in Example 10 of the present invention. DETAILED DESCRIPTION
[0040] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0041] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0042] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.
[0043] A specific embodiment of the present invention provides a nickel-based catalytic material and a preparation method thereof, the preparation method comprising the following steps:
[0044] S1. Ultrasonic cleaning of nickel foam with hydrochloric acid, ethanol and deionized water, and drying for later use. Pretreatment can remove stains and oxides on the surface of nickel foam, ensuring uniform growth of nanosheets during subsequent corrosion.
[0045] S2. Place the pretreated nickel foam in seawater containing a single transition metal salt and oscillate in a constant temperature oscillator. The strong penetration and depassivation properties of chloride ions in seawater are used to corrode nickel into nickel ions, and oxygen and carbon dioxide in the air are dissolved in seawater to participate in the reaction through oscillation to form hydroxide ions and carbonate ions, and then nickel ions, transition metal ions, hydroxide ions and carbonate ions are combined and synchronously precipitated on the surface of the nickel foam.
[0046] In a specific embodiment, the transition metal salt may be cobalt chloride, manganese chloride, iron chloride, molybdenum chloride, chromium chloride, copper chloride, etc., and its concentration in seawater is 0.5-50 mM. By introducing the transition metal component, the adsorption capacity of the catalytic material for the reaction substrate is improved, which greatly enhances the reaction activity of the catalytic material.
[0047] In a specific embodiment, the temperature of the constant temperature oscillator is 20-25°C, the oscillation frequency is 100-200 rpm, and the oscillation time is 0.5-16h. The oscillation conditions will affect the structure and phase of the nanosheets, so it is necessary to control the oscillation conditions to ensure the generation of layered bimetallic basic carbonates.
[0048] In this step, layered bimetallic basic carbonates are uniformly grown on the surface of nickel foam, which can provide active sites, enhance adsorption performance, and improve electron transfer pathways, thereby improving catalytic activity and stability.
[0049] S3. After shaking, the material is taken out from the seawater and rinsed to obtain a nickel-based catalytic material, which includes a foam nickel substrate, and the surface of the foam nickel substrate is evenly loaded with a bimetallic basic carbonate catalyst to form a semiconductor-metal heterojunction, which effectively improves the electron transfer path. The bimetallic basic carbonate catalyst has a flower-like nanosheet array structure or a needle-like structure, and has a high specific surface area and adsorption capacity.
[0050] The nickel-based catalytic material prepared by the above method is applied to the electrocatalytic oxidation of biomass materials such as 5-hydroxymethylfurfural, 2,5-furan dimethanol, and 2,5-tetrahydrofuran dimethanol, which can achieve efficient conversion of biomass materials. The specific operation method is to construct a three-electrode system, with the nickel-based catalytic material as the working electrode, the counter electrode is a platinum electrode or a carbon material electrode, the reference electrode is a Hg / HgO reference electrode, a saturated calomel electrode, or an Ag / AgCl reference electrode, the electrolyte is an alkaline solution, the biomass concentration is 5 to 100 mM, the reaction potential is 1.2 to 1.6 V vs. RHE, and the nickel-based catalytic material is highly selective for the reaction path of biomass oxidation.
[0051] The technical effects of the present invention are described below in conjunction with specific embodiments. Unless otherwise specified, the raw materials in the embodiments of the present application are purchased through commercial channels.
[0052] Example 1
[0053] 1) Cut the nickel foam into 3×0.5cm 2 size, ultrasonically cleaned in hydrochloric acid (1M), ethanol and deionized water for 10 minutes in sequence, dried for later use, and its surface structure is as follows Figure 1 As shown in (a) and (d).
[0054] 2) The pretreated nickel foam was placed in a seawater solution containing 5 mM CoCl2·6H2O and oscillated in a constant temperature oscillator at 25°C for 16 h at a frequency of 150 rpm. The nickel-based catalytic material Co-sw / NF was obtained, and its surface structure was as follows: Figure 1 As shown in (b) and (e), it presents a flower-like nanosheet array structure.
[0055] 3) Another portion of the pretreated nickel foam was placed in a seawater solution containing 5 mM MnCl2·4H2O and oscillated in a constant temperature oscillator at 25°C for 16 h at a frequency of 150 rpm. The nickel-based catalytic material Mn-sw / NF was obtained, and its surface structure was as follows: Figure 1 As shown in (c) and (f), it has a needle-like structure.
[0056] 4) The nickel-based catalytic material Co-sw / NF prepared in step 2) was subjected to HRTEM test, and the crystallization of the nanosheet structure on the substrate surface was as follows: Figure 2As shown in (a), fast Fourier transform (FFT) and inverse Fourier transform (iFFT) analysis show two lattice fringes with a d-spacing of and This is consistent with the d-spacing of (Co,Ni)O(OH). In addition, Figure 2 The selected area electron diffraction (SAED) pattern in (b) shows a group of Ni 0.75 Co 0.25 (CO3) 0.125 The (012), (110) and (113) planes of (OH)2!0.38H2O are aligned with unique lattice points, with spacings of and
[0057] 5) The nickel-based catalytic material Co-sw / NF prepared in step 2) was subjected to TG-FTIR test, and the results were as follows: Figure 3 shown. Figure 3 (a) is the TG mass loss curve of Co-sw / NF during the entire heating process. It can be observed that the process consists of three different stages, and the total mass loss rate is only 0.95%, which indicates that the corrosion process accounts for only a small part of the material. Combined with the real-time FTIR detection of the released gas during the TG heating process ( Figure 3 (b)), the mass change at 150 °C is attributed to the decomposition of hydroxides on the Co-sw / NF surface; the mass changes at 300 °C and 400 °C are attributed to the gradual decomposition of alkaline carbonates into CO2 and H2O, which further confirms that the substances generated on the nickel foam substrate belong to basic carbonates.
[0058] 6) The nickel-based catalytic material Co-sw / NF prepared in step 2) and the nickel-based catalytic material Mn-sw / NF prepared in step 3) were activated by cyclic voltammetry, with a low potential of 0.125 V vs. RHE, a high potential of 1.725 V vs. RHE, and a scanning number of 30 cycles.
[0059] 7) A three-electrode system was constructed, with nickel foam NF, activated Co-sw / NF and Mn-sw / NF as working electrodes, Hg / HgO as reference electrodes, and platinum sheet as counter electrodes. The electrolyte was 1M KOH, the electrolyte volume was 10mL, and the stirring speed was 600rpm. HMF was added to the electrolyte to a concentration of 0, 10, and 100mM. The electrochemical performance was evaluated at 5mV·s -1 Linear sweep voltammetry (LSV) was performed at a scan rate of 1:1 to test the electrochemical activity of NF, Co-sw / NF and Mn-sw / NF. The results are shown in Figure 4 shown. Figure 4(a) Current density diagram of NF, Co-sw / NF, and Mn-sw / NF at 1.425 V vs. RHE potential and 100 mM HMF concentration; Figure 4 (b), (c), and (d) are the LSV curves of NF, Co-sw / NF, and Mn-sw / NF under HMF concentrations of 0 mM, 10 mM, and 100 mM, respectively.
[0060] Example 2
[0061] 1) Cut the nickel foam into 3×0.5cm 2 The size was ultrasonically cleaned in hydrochloric acid (1 M), ethanol and deionized water for 10 min respectively and dried for later use.
[0062] 2) Five portions of pretreated nickel foams were placed in seawater solutions containing 0.5 mM, 1 mM, 5 mM, 10 mM, and 50 mM CoCl2·6H2O, respectively, and oscillated in a constant temperature oscillator at 25°C for 16 h at an oscillation frequency of 150 rpm to obtain five nickel-based catalytic materials Co-sw / NF.
[0063] 3) The five nickel-based catalytic materials Co-sw / NF prepared in step 2) were activated by cyclic voltammetry, with a low potential of 0.125 V vs. RHE, a high potential of 1.725 V vs. RHE, and a scanning number of 30 cycles.
[0064] 4) Construct a three-electrode system, with the five activated Co-sw / NF as working electrode, Hg / HgO reference electrode, and platinum counter electrode. The electrolyte is 1M KOH, the electrolyte volume is 10mL, and the stirring speed is 600rpm. HMF is added to the electrolyte to a concentration of 0, 10, and 100mM. -1 Linear sweep voltammetry was performed at a scan rate of 1.5 % to test the electrochemical activity of nickel-based catalytic materials prepared with different transition metal salt concentrations. The results are as follows: Figure 5 shown. Figure 5 (a) Current density diagram corresponding to five Co-sw / NFs at 1.425 V vs. RHE potential and 100 mM HMF concentration; Figure 5 (b), (c), and (d) are the LSV curves of five Co-sw / NFs under HMF concentrations of 0 mM, 10 mM, and 100 mM, respectively. The results show that the electrochemical activity of the prepared nickel-based catalytic material is optimal when the transition metal salt concentration is 5 mM.
[0065] Example 3
[0066] 1) Cut the nickel foam into 3×0.5cm 2The size was ultrasonically cleaned in hydrochloric acid (1 M), ethanol and deionized water for 10 min respectively and dried for later use.
[0067] 2) Four portions of pretreated nickel foam were placed in a seawater solution containing 5 mM CoCl2·6H2O, and oscillated in a constant temperature oscillator at 25°C for 0.5 h, 2 h, 8 h, and 16 h, respectively, with an oscillation frequency of 150 rpm, to obtain four nickel-based catalytic materials Co-sw / NF.
[0068] 3) The four nickel-based catalytic materials Co-sw / NF prepared in step 2) were activated by cyclic voltammetry, with a low potential of 0.125 V vs. RHE, a high potential of 1.725 V vs. RHE, and a scanning number of 30 cycles.
[0069] 4) Construct a three-electrode system, with the four activated Co-sw / NF as working electrode, Hg / HgO reference electrode, and platinum counter electrode. The electrolyte is 1M KOH, the electrolyte volume is 10mL, and the stirring speed is 600rpm. HMF is added to the electrolyte to a concentration of 0, 10, and 100mM. -1 Linear sweep voltammetry was performed at a scan rate to test the electrochemical activity of nickel-based catalytic materials prepared at different corrosion times. The results are as follows Figure 6 shown. Figure 6 (a) Current density diagram corresponding to four Co-sw / NFs at 1.425 V vs. RHE potential and HMF concentration of 100 mM; Figure 6 (b), (c), and (d) are the LSV curves of four types of Co-sw / NF under the conditions of HMF concentration of 0mM, 10mM, and 100mM, respectively. The results show that the electrochemical activity of the prepared nickel-based catalytic material is optimal when the corrosion time is 2h.
[0070] Example 4
[0071] 1) Cut the nickel foam into 3×0.5cm 2 The size was ultrasonically cleaned in hydrochloric acid (1 M), ethanol and deionized water for 10 min respectively and dried for later use.
[0072] 2) The pretreated nickel foam was placed in a seawater solution containing 5 mM CoCl2·6H2O, and oscillated in a constant temperature oscillator at 25°C for 2 hours with an oscillation frequency of 150 rpm to obtain a nickel-based catalytic material Co-sw / NF.
[0073] 3) Another portion of the pretreated nickel foam was placed in a seawater solution containing 5 mM MnCl2·4H2O, and oscillated in a constant temperature oscillator at 25°C for 2 hours with an oscillation frequency of 150 rpm to obtain a nickel-based catalytic material Mn-sw / NF.
[0074] 4) The nickel-based catalytic material Co-sw / NF prepared in step 2) and the nickel-based catalytic material Mn-sw / NF prepared in step 3) were activated by cyclic voltammetry, with a low potential of 0.125 V vs. RHE, a high potential of 1.725 V vs. RHE, and a scanning number of 30 cycles.
[0075] 5) A three-electrode system was constructed, with activated Co-sw / NF and Mn-sw / NF as working electrodes, Hg / HgO as reference electrode, and platinum sheet as counter electrode. The electrolyte was 1M KOH, the electrolyte volume was 10mL, and the stirring speed was 600rpm. HMF was added to the electrolyte to a concentration of 0, 10, and 100mM. The electrochemical performance was evaluated at 5mV·s -1 The linear sweep voltammetry (LSV) test was performed at a scan rate of Figure 7 In pure electrolyte, both Co-sw / NF and Mn-sw / NF electrodes showed obvious oxidation peaks. Co-sw / NF -2 The onset potential at the current density (0.976 V vs. RHE) is lower than that of Mn-sw / NF (1.304 V vs. RHE). The addition of HMF further reduces the onset potential of Co-sw / NF and Mn-sw / NF electrodes, accompanied by a significant increase in current density. In the absence of HMF, Co-sw / NF and Mn-sw / NF electrodes require an applied potential of 1.596 V vs. RHE and 1.700 V vs. RHE to reach 50 mA cm -2 In 10 mM HMF, the required potentials dropped to 1.356 V vs. RHE and 1.375 V vs. RHE, respectively, indicating that the oxidation of HMF is significantly easier than OER.
[0076] Example 5
[0077] 1) Cut the nickel foam into 3×0.5cm 2 The size was ultrasonically cleaned in hydrochloric acid (1 M), ethanol and deionized water for 10 min respectively and dried for later use.
[0078] 2) The pretreated nickel foam was placed in a seawater solution containing 5 mM CoCl2·6H2O, and oscillated in a constant temperature oscillator at 25°C for 2 hours with an oscillation frequency of 150 rpm to obtain a nickel-based catalytic material Co-sw / NF.
[0079] 3) The nickel-based catalytic material Co-sw / NF prepared in step 2) was activated by cyclic voltammetry, with a low potential of 0.125 V vs. RHE, a high potential of 1.725 V vs. RHE, and a scanning number of 30 cycles.
[0080] 4) Construct a three-electrode system with activated Co-sw / NF as the working electrode, Hg / HgO as the reference electrode, and platinum as the counter electrode. The electrolyte is 1M KOH, the electrolyte volume is 10mL, and the stirring speed is 600rpm. HMF is added to the electrolyte to a concentration of 10mM.
[0081] 5) Electrolysis experiments were conducted to test the HMF conversion, FDCA yield and Faradaic efficiency (FE) at electrolysis potentials of 1.375, 1.400, 1.425, 1.450 and 1.475 V vs. RHE. The results are shown in Figure 5. Figure 8 and Fig. 9 shown. Figure 8 Shows the products generated at different electrolysis potentials. Fig. 9 (a) shows the time course of HMF electrolysis at a potential of 1.375 V vs. RHE. Fig. 9 (b) shows the time course of electrolysis of HMF at a potential of 1.400 V vs. RHE. Fig. 9 (c) shows the time course of HMF electrolysis at a potential of 1.425 V vs. RHE. Fig. 9 (d) shows the time course of HMF electrolysis at a potential of 1.450 V vs. RHE. Fig. 9 (e) shows the time course of electrolysis of HMF at 1.475V vs.RHE. The results show that the HMF conversion rate, FDCA yield and FE all reach the optimal value at 1.425V vs.RHE, and it can be seen that the higher the electrolysis potential, the lower the content of the intermediate product HMFCA during the reaction, indicating that high potential promotes the conversion of HMFCA to FFCA. At the same time, since HMFCA and OER are in a competitive relationship during the electrolysis process, too high a potential will aggravate OER and produce more side reactions, resulting in a decrease in product yield. Co-sw / NF can completely convert 10mM HMF at 1.425V vs.RHE for 1.74h, and the FDCA yield reaches 97.39%, and the FE is 97.32%, and the carbon balance is 97.39%.
[0082] Example 6
[0083] 1) Cut the nickel foam into 3×0.5cm 2 The size was ultrasonically cleaned in hydrochloric acid (1 M), ethanol and deionized water for 10 min respectively and dried for later use.
[0084] 2) The pretreated nickel foam was placed in a seawater solution containing 5 mM MnCl2·4H2O, and oscillated in a constant temperature oscillator at 25°C for 2 hours with an oscillation frequency of 150 rpm to obtain a nickel-based catalytic material Mn-sw / NF.
[0085] 3) The nickel-based catalytic material Mn-sw / NF prepared in step 2) was activated by cyclic voltammetry, with a low potential of 0.125 V vs. RHE, a high potential of 1.725 V vs. RHE, and a scanning number of 30 cycles.
[0086] 4) A three-electrode system was constructed, with activated Mn-sw / NF as the working electrode, Hg / HgO as the reference electrode, and platinum as the counter electrode. The electrolyte was 1M KOH, the electrolyte volume was 10 mL, and the stirring speed was 600 rpm. HMF was added to the electrolyte to a concentration of 10 mM.
[0087] 5) Conduct electrolysis experiments at an electrolysis potential of 1.425 V vs. RHE to test the conversion rate of HMF, FDCA yield and Faradaic efficiency (FE). The results are as follows: Fig.10 As shown, the theoretical coulomb amount (57.891C) required for electrolysis was reached in 2.16 h, the HMF conversion rate was 98.46%, the FDCA yield was 86.96%, the FE was 86.10%, and the carbon balance was 85.94%.
[0088] Example 7
[0089] 1) Cut the nickel foam into 3×0.5cm 2 The size was ultrasonically cleaned in hydrochloric acid (1 M), ethanol and deionized water for 10 min respectively and dried for later use.
[0090] 2) The pretreated nickel foam was placed in a seawater solution containing 5 mM CoCl2·6H2O, and oscillated in a constant temperature oscillator at 25°C for 2 hours with an oscillation frequency of 150 rpm to obtain a nickel-based catalytic material Co-sw / NF.
[0091] 3) The nickel-based catalytic material Co-sw / NF prepared in step 2) was activated by cyclic voltammetry, with a low potential of 0.125 V vs. RHE, a high potential of 1.725 V vs. RHE, and a scanning number of 30 cycles.
[0092] 4) Construct a three-electrode system with activated Co-sw / NF as the working electrode, Hg / HgO as the reference electrode, and platinum as the counter electrode. The electrolyte is 1M KOH, the electrolyte volume is 10mL, and the stirring speed is 600rpm. HMF is added to the electrolyte to a concentration of 10mM.
[0093] 5) Conducting electrolysis experiments at an electrolysis potential of 1.425 V vs. RHE to test the conversion rate of HMF, FDCA yield and Faradaic efficiency (FE).
[0094] 6) After the electrolysis is completed, rinse the Co-sw / NF working electrode with deionized water and repeat steps 4) and 5) to perform the electrolysis cycle test. Fig.11 As shown, after 5 cycles of electrolysis, the performance of Co-sw / NF is still excellent, with HMF conversion still reaching 98.88%, FDCA yield 96.85%, FE 91.51%, and carbon balance 98.81%.
[0095] Example 8
[0096] 1) Cut the nickel foam into 3×0.5cm 2 The size was ultrasonically cleaned in hydrochloric acid (1 M), ethanol and deionized water for 10 min respectively and dried for later use.
[0097] 2) The pretreated nickel foam was placed in a seawater solution containing 5 mM CoCl2·6H2O, and oscillated in a constant temperature oscillator at 25°C for 2 hours with an oscillation frequency of 150 rpm to obtain a nickel-based catalytic material Co-sw / NF.
[0098] 3) The nickel-based catalytic material Co-sw / NF prepared in step 2) was activated by cyclic voltammetry, with a low potential of 0.125 V vs. RHE, a high potential of 1.725 V vs. RHE, and a scanning number of 30 cycles.
[0099] 4) A three-electrode system was constructed, with the activated Co-sw / NF as the working electrode, Hg / HgO as the reference electrode, and a platinum sheet as the counter electrode. The electrolyte was 1 M KOH, the electrolyte volume was 10 mL, and the stirring speed was 600 rpm.
[0100] 5) At 10 mA cm -2 The constant current test was carried out under the current density, and the results were as follows Fig.12 As shown, it can be seen that after 50 hours of continuous chronopotentiometry, the potential has no obvious decay, and the good morphology and nanosheet array structure can still be maintained after the stability test, which indicates that the nickel-based catalytic material Co-sw / NF has good stability.
[0101] Example 9
[0102] 1) Cut the nickel foam into 3×0.5cm 2 The size was ultrasonically cleaned in hydrochloric acid (1 M), ethanol and deionized water for 10 min respectively and dried for later use.
[0103] 2) The pretreated nickel foam was placed in a seawater solution containing 5 mM CoCl2·4H2O, and oscillated in a constant temperature oscillator at 25°C for 2 hours with an oscillation frequency of 150 rpm to obtain a nickel-based catalytic material Co-sw / NF.
[0104] 3) The nickel-based catalytic material Co-sw / NF prepared in step 2) was activated by cyclic voltammetry, with a low potential of 0.125 V vs. RHE, a high potential of 1.725 V vs. RHE, and a scanning number of 30 cycles.
[0105] 4) A three-electrode system was constructed, with activated Co-sw / NF as the working electrode, Hg / HgO as the reference electrode, and platinum as the counter electrode. The electrolyte was 1M KOH, the electrolyte volume was 5mL, and the stirring speed was 600rpm. BHMF was added to the electrolyte to a concentration of 10mM.
[0106] 5) Conduct electrolysis experiments at an electrolysis potential of 1.450 V vs. RHE to test the conversion rate of BHMF, FDCA yield and Faradaic efficiency (FE). The results are as follows: Fig.13 As shown, the BHMF conversion was 98.75%, the FDCA yield was 92.76%, the FE was 88.20%, and the carbon balance was 96.23%.
[0107] Example 10
[0108] 1) Cut the nickel foam into 3×0.5cm 2 The size was ultrasonically cleaned in hydrochloric acid (1 M), ethanol and deionized water for 10 min respectively and dried for later use.
[0109] 2) The pretreated nickel foam was placed in a seawater solution containing 5 mM CoCl2·4H2O, and oscillated in a constant temperature oscillator at 25°C for 2 hours with an oscillation frequency of 150 rpm to obtain a nickel-based catalytic material Co-sw / NF.
[0110] 3) The nickel-based catalytic material Co-sw / NF prepared in step 2) was activated by cyclic voltammetry, with a low potential of 0.125 V vs. RHE, a high potential of 1.725 V vs. RHE, and a scanning number of 30 cycles.
[0111] 4) A three-electrode system was constructed, with activated Co-sw / NF as the working electrode, Hg / HgO as the reference electrode, and platinum as the counter electrode. The electrolyte was 1M KOH, the electrolyte volume was 5mL, and the stirring speed was 600rpm. THFDM was added to the electrolyte to a concentration of 40mM.
[0112] 5) Conduct electrolysis experiments at an electrolysis potential of 1.525 V vs. RHE to test the conversion rate of THFDM, the yield of THFDCA and the Faradaic efficiency (FE). The results are as follows: Fig.14 As shown, the THFDM conversion was 99.48%, the THFDCA yield was 93.20%, the FE was 91.14%, and the carbon balance was 94.54%.
[0113] Although the present invention is disclosed as above, the protection scope of the present invention is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will fall within the protection scope of the present invention.
Claims
1. A method for preparing a nickel-based catalytic material, characterized in that: The following steps are involved: The nickel foam was ultrasonically cleaned with hydrochloric acid, ethanol and deionized water, and dried for later use; The pretreated nickel foam is placed in seawater containing a single transition metal salt and oscillated in a constant temperature oscillator; After shaking, the material is taken out from the seawater and rinsed to obtain a nickel-based catalytic material.
2. The method for preparing a nickel-based catalytic material according to claim 1, characterized in that: The concentration of the transition metal salt in the seawater is 0.5-50 mM.
3. The method for preparing a nickel-based catalytic material according to claim 2, characterized in that: The transition metal salt is selected from one of cobalt chloride, manganese chloride, iron chloride, molybdenum chloride, chromium chloride and copper chloride.
4. The method for preparing a nickel-based catalytic material according to claim 1, characterized in that: The oscillation frequency of the constant temperature oscillator is 100-200 rpm.
5. The method for preparing a nickel-based catalytic material according to claim 4, characterized in that: The oscillation time in the constant temperature oscillator is 0.5 to 16 hours.
6. The method for preparing a nickel-based catalytic material according to claim 5, characterized in that: The temperature of the constant temperature oscillator is 20-25°C.
7. A nickel-based catalytic material prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The invention comprises a foamed nickel substrate and a bimetallic basic carbonate catalyst loaded on the surface of the foamed nickel substrate.
8. The nickel-based catalytic material according to claim 7, characterized in that: The bimetallic basic carbonate catalyst is in a flower-like nanosheet array structure or a needle-like structure.
9. A use of the nickel-based catalytic material as claimed in claim 7, characterized in that: The nickel-based catalytic material is used for electrocatalytic oxidation of biomass, wherein the biomass is selected from one of 5-hydroxymethylfurfural, 2,5-furan dimethanol and 2,5-tetrahydrofuran dimethanol.
10. The use according to claim 9, characterized in that: The reaction system of the electrocatalytic oxidation is a three-electrode system, the working electrode is the nickel-based catalytic material, the counter electrode is a platinum electrode or a carbon material electrode, the reference electrode is selected from one of a Hg / HgO reference electrode, a saturated calomel electrode, and an Ag / AgCl reference electrode, the electrolyte is an alkaline solution, the concentration of the biomass is 5 to 100 mM, and the reaction potential is 1.2 to 1.6 V vs. RHE.